Improving Public Health Independence in The Use of Moringa Leaf (Moringa Oleifera) For Breast Swelling and Increasing Breast Milk Production - Prastyoningsih, Aris; Frieda Ani Noor; Wahyuningsih Safitri; Ajeng Maharani; Lenny Blegur; Tresia Umarianti (IJCS: International Journal of Community Service, 2023)
There are many factors that influence the nutritional status of under-fives, including income, knowledge of mother's nutrition, access to health services, incidence of diarrhea, exclusive breastfeeding, clean water sources, parenting style, nutrition during pregnancy and low birth weight babies. LBW). Success in exclusive breastfeeding is influenced by a mother's ability to deal with problems in breastfeeding. The purpose of this community service is to optimize the independence of public health in the use of Moringa leaves for breast swelling and to facilitate the production of breast milk as an effort to support the success of exclusive breastfeeding. The target of community service activities are all members of the community, mothers of health cadres, postpartum and breastfeeding mothers, posyandu mothers in Kajoran Klaten Selatan village on Saturday, July 1, 2023 and communities in foreign partners (ICS) Tuesday, June 27 2023. From the results of monitoring evaluation there was an increase in knowledge about the use of Moringa leaves for the management of breast swelling and Increased participant skills in using Moringa leaves for the management of breast swelling by 88%.